Comparative endoscopic techniques of medial rectus muscle retraction for approaching intraconal tumors: Our experience with five cases - Chen, Linli; Yan, Xiaorong; Fu, Yunshan; Wang, Tingting; Zhan, Zhiyun; Ye, Shengnan; Jiang, Changzhen; Chen, Guohao (Frontiers in Surgery, 2022)
Objective To examine the role of transnasal endoscopic approaches in the management of intraconal tumors and demonstrate the use of an eyelid speculum in comparison with different techniques of medial rectus muscle (MRM) retraction. Methods Retrospective data of five patients with intraconal tumors operated on and followed up by the senior authors between December 2019 and April 2022 was collected. Presenting symptoms, technical details, imaging and histology findings, outcomes, and complications were evaluated. Results Four primary and one recurrent tumor were identified. The mean patient age was 50 (range, 29–64) years. One tumor was located lateral to the optic nerve, one central and three medial. A complete surgical resection was obtained in four primary cases and a partial resection was achieved in the recurrent case. The MRM was retracted using three different techniques: (1) an infant eyelid speculum creating an operative window between the medial and inferior rectus muscle, (2) external MRM disinsertion transconjunctivally, (3) a four-handed technique performed transseptally by two surgeons. Transient postoperative ophthalmoplegia was recorded in four cases and transient ptosis in one. Three patients completely recovered in 2–3 months while one undergoing MRM disinsertion ended up in restricted strabismus at 15-month follow-up. No other long-term complications have been noted in all five patients with a mean follow-up of 22 (range, 14–32) months. No patients with primary tumors have required additional surgery for tumor recurrence. Conclusion The indication of endoscopic intraconal surgery may expand to lesions lateral to the optic nerve when the nerve is not in its natural position. The well-known advantages of the endoscopic techniques, namely the lack of external scars, better visualization, less bleeding, and fewer complications, were confirmed. An eye speculum provides a better surgical corridor and eases the pressure exerted on the MRM, which has a promising application prospect.